Changes in selenium levels in epilepsy (2005)
Introduction. It has been suggested that antiepileptic drug therapies deplete total body selenium stores and failure to give appropriate selenium supplementation, especially to patients receiving valproic acid during pregnancy may increase the risk of neural tube defects or other free radical mediated damage. Selenium is essential for the synthesis of selenoproteins, including glutathione peroxidase. Aims. To review the present state of knowledge about selenium behaviour in people with epilepsy taking antiepileptic drugs and to develop guidelines for the appropriate use of selenium supplements. Development. Databases such as Medline, Embase, Scisearch and Lilacs were consulted to have access to literature. A search in said databases was performed in order to find articles published from January 1966 to August 2004. All articles published in English and Spanish were considered. A manual review of the references present in each produced article was done in order to identify the articles that the electronic search may have not found itself. The title and abstract of the potential articles were analyzed before asking for the complete article. However, articles which seemed ambiguous were completely analyzed later to establish their relevance. Conclusions. There is insufficient evidence to fully evaluate the effect of selenium supplementation. The possible beneficial effects on pregnancy need to be evaluated in further studies. © 2005, Revista de Neurología.